Coastal Clean Up sebagai Upaya Penguatan Strategi Pengelolaan Kawasan Konservasi Pesisir dan Pulau-pulau Kecil (KKP3K) Paloh Kalimantan Barat - Yuliono, Agus; Safitri, Ikha; Sofiana, Mega Sari Juane; Susanto, Hendro; Zulfian, Zulfian (Indonesian Journal Publisher, 2024)
Paloh District is a coastal area which directly borders to Sarawak (Malaysia) and the Natuna Sea. This area has the potential for marine and coastal resources, such as mangrove ecosystems, coral reefs and turtles, so it has been designated as one of the conservation areas in West Kalimantan. To date, in the management of KKP3K Paloh, there are still many challenges, one of them is plastic waste contamination. Plastic waste is a global and very complex problem, because it can have a negative impact on biota, ecosystems and human health. The results of a report from BKSDA in collaboration with the WWF-Indonesia Foundation, found that 21 young turtles were died on Paloh Beach, West Kalimantan due to plastic waste was found in their digestive tract. Plastic accumulation in the aquatic environment occurs when the rate of input of plastic pollution into an area exceeds the rate of natural removal processes. Therefore, it is needed an action to reduce the amount of plastic waste accumulated in coastal and marine areas. This activity aimed to reduce the amount of plastic waste on Sungai Belacan Beach, Paloh District, West Kalimantan. Apart from that, this activity was an effort to strengthen the management strategy for the Coastal and Small Islands Conservation Area (KKP3K) in Paloh, West Kalimantan. Community Service Activities were carried out at Sungai Belacan Beach. The results found the waste types consisting of plastic bottles, glass bottles, medicine bottles, drink cups/packaging, food and beauty product packaging, stereofoam, plastic bags and ropes, fishermen's fishing gear, and wood. Plastic waste has the highest percentage (95%), then wood waste (3%), and other types of waste (2%).